1998
DOI: 10.1111/j.1600-0447.1998.tb09998.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological morbidity and HIV in Kenya

Abstract: This paper describes a cross-sectional study with subjects and raters blind to HIV status to assess psychiatric morbidity associated with HIV in a sample of working adults in Western Kenya. Subjects were recruited from an occupational health clinic for statutory annual health checks of workers in the food industry. Psychiatric interviews and neuropsychological tests were conducted. Of 230 subjects, 34% were HIV positive. Women had a higher rate than men, and those who worked as bargirls or were divorced, widow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The social, economic and health impact of depression in sub-Saharan Africa is also great, where depression is associated with mortality [2][3][4][5] , work disability [4][5][6][7] , lower quality of life 5,[8][9][10][11][12] , risk of heart disease 13 and high-risk behaviors for contracting HIV infection 14 . With one exception 15 , the sparse literature on depression among individuals living with HIV/AIDS in sub-Saharan Africa has shown elevated rates of depression relative to community samples 3,8,10,[16][17][18][19][20][21][22][23][24][25] , consistent with western countries [26][27][28][29] . Thus, there is an urgency to incorporating mental health into HIV/ AIDS treatment programs in sub-Saharan Africa, including western Kenya [30][31][32][33][34][35] .…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The social, economic and health impact of depression in sub-Saharan Africa is also great, where depression is associated with mortality [2][3][4][5] , work disability [4][5][6][7] , lower quality of life 5,[8][9][10][11][12] , risk of heart disease 13 and high-risk behaviors for contracting HIV infection 14 . With one exception 15 , the sparse literature on depression among individuals living with HIV/AIDS in sub-Saharan Africa has shown elevated rates of depression relative to community samples 3,8,10,[16][17][18][19][20][21][22][23][24][25] , consistent with western countries [26][27][28][29] . Thus, there is an urgency to incorporating mental health into HIV/ AIDS treatment programs in sub-Saharan Africa, including western Kenya [30][31][32][33][34][35] .…”
Section: Introductionmentioning
confidence: 83%
“…The PHQ-9 scoring algorithm for DSM-IV diagnoses of MDD and ODD is described elsewhere (p. 607) 57 . The PHQ-9 total score ranges from 0 to 27 with five severity categories: minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19) and severe (20)(21)(22)(23)(24)(25)(26)(27). General health perception rating was administered 85 : "In general how would you rate your overall health right now?"…”
Section: Methodsmentioning
confidence: 99%
“…In Zimbabwe, Sebit et al [9] found that 71.3% of the HIV-positive subjects suffered from psychiatric disorders compared with 44.3% of HIVnegative controls, whereas in Kenya, no substantial differences in psychiatric morbidity, including depression or performance on neuropsychological tests, were found between HIV-positive workers and HIV-negative controls [10]. These studies have been limited either by not using a standardized interview to make a diagnosis of psychiatric disorders [9] or by other methodological problems [10]. There is a need to distinguish between clear psychiatric disorders (which need prompt referral and treatment) and subsyndromal symptoms (which may be a normal response to the HIV infection).…”
Section: Introductionmentioning
confidence: 96%
“…However, in another study conducted in this country, researchers did not report significantly different levels of psychiatric morbidity when comparing a group of adults based on their HIV serostatus (Carson et al, 1998).…”
Section: Introductionmentioning
confidence: 96%